Report of the Study Team on Tribal Development Programmes Andaman and Nicobar Islands - Planning Commission (Planning Commission, Government of India, 1970)
The Study Team Report on Tribal Development Programmes in the Andaman & Nicobar Islands evaluates strategies for the welfare of the region’s diverse Scheduled Tribes, which constitute over 22% of the population. The report highlights low literacy rates, reliance on household industries, and subsistence lifestyles among isolated tribes, underscoring the need for culturally sensitive interventions. Key recommendations include establishing a dedicated tribal development cell, conducting detailed socio-economic surveys, enhancing education and health facilities, improving agricultural productivity and livestock management, and upgrading transportation and communication infrastructure. The report emphasizes active engagement, tailored development programs, and sustainable administrative measures as essential to promoting tribal empowerment and preserving cultural heritage in the islands.
Committee on Plan Projects Planning Commission
Committee on Plan Projects Planning Commission
Keywords: Tribal Development; Andaman & Nicobar Islands; Scheduled Tribes; Cultural Sensitivity; Education Enhancement; Health Services; Agricultural Development; Livestock Management; Infrastructure Improvement; Socio-Economic Surveys; Government Policy; Community Engagement